Electronic Tools for English Language Education (with a special view to English for Specific Purposes) - Feketéné Silye, Magdolna (Acta Agraria Debreceniensis, 2002)
Almost simultaneously with the developments in information technology over the past fifteen to twenty years, literacy has gained new dimensions. To be considered literate in our age demands functional, academic, critical and technological skills. Because language and technology are inseparable in this context, technology as a means for developing literacy skills must be an integral part of the language class. This paper examines some of the ways electronic tools can be of use in developing student language literacy competences, with a special emphasis on the benefits learners of English for Specific Purposes can reap.